Stress-driven cardiac calcium mishandling via a kinase-to-kinase crosstalk - McKee, Charia (Pflugers Arch, 2021)
Calcium homeostasis in the cardiomyocyte is critical to the regulation of normal cardiac function. Abnormal calcium dynamics such as altered uptake by the sarcoplasmic reticulum (SR) Ca(2+)-ATPase and increased diastolic SR calcium leak are involved in the development of maladaptive cardiac remodeling under pathological conditions. Ca(2+)/calmodulin-dependent protein kinase II-δ (CaMKIIδ) is a well-recognized key molecule in calcium dysregulation in cardiomyocytes. Elevated cellular stress is known as a common feature during pathological remodeling, and c-jun N-terminal kinase (JNK) is an important stress kinase that is activated in response to intrinsic and extrinsic stress stimuli. Our lab recently identified specific actions of JNK isoform 2 (JNK2) in CaMKIIδ expression, activation, and CaMKIIδ-dependent SR Ca(2+) mishandling in the stressed heart. This review focuses on the current understanding of cardiac SR calcium handling under physiological and pathological conditions as well as the newly identified contribution of the stress kinase JNK2 in CaMKIIδ-dependent SR Ca(2+) abnormal mishandling. The new findings identifying dual roles of JNK2 in CaMKIIδ expression and activation are also discussed in this review.